Case control study of nucleated RBC’s in cord blood as a predictor of perinatal asphyxia its severity and outcome - Khurana, Mandeep Singh; Arora, Sunita; Malik, Supriya; Gulati, Jasgobind Singh (International Journal of Contemporary Pediatrics, 2017)
Background: Perinatal asphyxia word derived from the greek word a-spyxos, meaning born without an evident pulse, is one of the most important causes of fetal distress. Inspite of major advances in technology and knowledge of fetal and perinatal medicine, it is one of the significant causes of mortality and long-term morbidity. World health organization (WHO) has defined perinatal asphyxia as a failure to initiate and sustain breathing at birth. HIE is one of the most common complication in an asphyxiated neonate because of its serious longterm neuromotor sequalae among the survivors. A detailed classification of HIE staging in term neonate was proposed by Sarnat and Sarnat. Methods: The present study was prospective case control study conducted in neonatal intensive care unit of Department of Pediatrics at SGRD institute of medical sciences and research over a period of one year from September 2016 to august 2017. Total of 100 newborns among which 50 asphyxiated babies were designated to case group and rest 50 normal term babies to control group. The NRBC count of the case and control groups is compared. The NRBC’s of subjects belonging to different stages of HIE is then compared. The results were analysed statistically chi-square analysis for variance (qualitative analysis), t-test (compare mean NRBC’s in different stages) by SPSS version 20 software for biostatistic and p-value of <0.05 was considered statistically significant. Results: Among total 100 babies included in the study, the male and female distribution was 22 (44%) and 28 (56%) in cases and 23 (46%) and 27 (54%) in controls respectively. In our study, the NRBC /100 WBC count for normal newborn was 0.88±1.35 and in case group it was 21.40±20. Conclusions: In present study, the cord blood NRBC count was shown to be a good predictor of perinatal asphyxia with sensitivity of 86%, specificity of 100%, positive predictive value of 100% and negative predictive value of 87.72%. NRBC’s can be used for early detection of HIE and its grading in asphyxiated neonates.